Spanish congresses on library and information science: from the inevitable fragmentation to the necessary transversality - Abadal, Ernest; Baiget, Tomí s (Anuario ThinkEPI, 2010)
The sophistication of society and the scientific specialization lead to the fragmentation of the groups and the audiences. With congresses happens the same and in this paper the organization of more general and cross-discipline conferences is proposed. A review of the evolution of the congresses and their characteristics over the past 15 years in Spain is done. In the annex the main Spanish congresses are listed.
Keywords: Conferences; Congresses; Symposia; Evolution; Spain; Specialization; Fragmentation; Transversality; Cross-discipline meetings; Library and information science.